A literature review on quantitative models for supply chain risk management: Can they be applied to pandemic disruptions?. (August 2022) - Rinaldi, Marta; Murino, Teresa; Gebennini, Elisa; Morea, Donato; Bottani, Eleonora
Highlights: A systematic review of supply chain risk management and disruptions is proposed. The focus is on quantitative models and pandemic emergencies. The usability of the available models for managing pandemic emergencies is evaluated. Limitations of the existing models and future research directions are suggested. Abstract: Supply chain risk management is considered a topic of increasing interest worldwide and its focus has evolved over time. The recent coronavirus pandemic (known as COVID-19) has forced business to handle a new global crisis and rapidly adapt to unexpected challenges. In an attempt to help companies counteract the pandemic risk, as well as to fuel the scientific discussion about this topic, this paper proposes a systematic literature review on risk management and disruptions in the supply chain focusing on quantitative models and paying a particular attention to highlighting the potentials of the studies reviewed for being applied to counteract pandemic emergencies. An appropriate query was made on Scopus and returned, after a manual screening, a useful set of 99 papers that proposed models for supply chain risk management. The relevant aspects of pandemics risk management have been first identified and mapped; then, the studies reviewed have been analysed with the aim of evaluating their suitability of being applied to sanitary crises. In carrying out this review of the literature, the study moves from previous, more general, reviews about risk management and updates them, starting from the lines of research that have been covered in recent years and evaluating their consistency with future research directions emerging also as a consequence of the pandemic crisis. Gaps and limitations of the existing models are identified and future research directions for pandemics risk management are suggested.